2019
DOI: 10.1002/pen.25106
|View full text |Cite
|
Sign up to set email alerts
|

Chain extension of polyamide 6/organoclay nanocomposites

Abstract: Thermal degradation of polyamide 6 (PA6)/organoclay nanocomposites is a serious impediment to wider applications of these nanocomposites. In this study, a solution is proposed based on the well‐established use of chain extenders. As in PA6, thermal degradation, in the absence of moisture, produces broken polymer chains with amide end groups, a chain extender with anhydride functionalities, known to be strongly reactive with amide groups, was used to reconnect the chains. Experiments conducted using a laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 36 publications
0
13
0
1
Order By: Relevance
“…In the absence of water as it is the case in practice during industrial extrusion, scission of the thermally weakest bond, the alkyl‐amide linkage, occurs resulting in amide end group (OCNH 2 ) and vinyl end group (CHCH 2 ) smaller chains . All the evidence to date from previous research and our most recent work is that the amide functionality is the one which is the most reactive (see work by Loontjens and Plum , Buccella et al , and Tuna ). Thus, an effective chain extender for PA6 thermally degraded in the absence of water is one that has high amide reactivity.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…In the absence of water as it is the case in practice during industrial extrusion, scission of the thermally weakest bond, the alkyl‐amide linkage, occurs resulting in amide end group (OCNH 2 ) and vinyl end group (CHCH 2 ) smaller chains . All the evidence to date from previous research and our most recent work is that the amide functionality is the one which is the most reactive (see work by Loontjens and Plum , Buccella et al , and Tuna ). Thus, an effective chain extender for PA6 thermally degraded in the absence of water is one that has high amide reactivity.…”
Section: Introductionmentioning
confidence: 77%
“…The recycled pellets were then dried in a vacuum oven at 80°C for 12 h ready for chain extension in the twin extruder. The chain extender‐PA6 dosage was kept constant at 1 wt% deemed to be sufficient from previous work , noting that the stochiometry of the polymer chain extension reaction is such that very little chain extender is required. Also from preliminary trials, zones temperature profile of 230–260–260–260–260°C and screw speed of 100 rpm were found to produce stable extrusion conditions.…”
Section: Methodsmentioning
confidence: 99%
“…PBT/1.5 EPO örneğinde karbonil grubuna ait 1711cm -1 'deki pikin (C=O gerilmesi) yüksekliğinde azalma, diğer örneklerin spektrumlarında ise değişimin olmadığı görülmektedir. Bu bulgu, termal bozunma ve düşük zincir uzatıcı konsantrasyonlarının örneklerin FTIR spektrumunda değişimlerin izlenmesine olanak vermemesi şeklinde yorumlanabilir [33,34]. Gd.…”
Section: Bulgular Ve Tartişmaunclassified
“…The results showed that the nanocomposites produced in the presence of a chain extender had a significant increase in the complex viscosity and the storage modulus. [ 24 ]…”
Section: Introductionmentioning
confidence: 99%